Security in Computing and Communications International Symposium, SSCC 2013, Mysore, India, August 22-24, 2013. Proceedings - Thampi, Sabu M.; Atrey, Pradeep K.; Fan, Chun-I.; Perez, Gregorio Martinez; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Symposium on Security in Computing and Communications, SSCC 2013, held in Mysore, India, in August 2013. The 24 revised full papers presented together with 15 poster papers were carefully reviewed and selected from 111 submissions. The papers cover all aspects of secure computing and communication in networking and distributed systems such as cloud-based data centers.
A Novel Approach for a Hardware-Based Secure Process Isolation in an Embedded System -- Signature Embedding in the Functional Description of Reversible -- Circuit -- Detecting Laser Fault Injection for Smart Cards Using Security Automata -- Virtual World Authentication Using the Smart Card Web Server -- A More Efficient and Secure Authentication Scheme over Insecure Networks Using Smart Cards -- A Combined Crypto-steganographic Approach for Information Hiding in Audio Signals Using Sub-band Coding, Compressive Sensing and Singular Value Decomposition.
Keywords: Computer science; Computer Communication Networks; Data protection; Computer Science; Systems and Data Security; Computer Communication Networks; e-Commerce/e-business.